Safety of IBI‐10090 for inflammation associated with cataract surgery: Phase 3 multicenter study. Issue 10 (October 2018) - Donnenfeld, Eric D.; Solomon, Kerry D.; Matossian, Cynthia
Abstract : Purpose : To compare the safety and efficacy of IBI‐10090 anterior chamber intracameral dexamethasone drug‐delivery suspension (Dexycu) with those of prednisolone acetate 1.0% ophthalmic drops in treating inflammation after cataract surgery. Setting : Eleven centers in the United States. Design : Prospective randomized open‐label multicenter trial. Methods : Patients were randomized 2:1 to receive a 5 μL injection of 517 μg IBI‐10090 in the anterior eye chamber or topical prednisolone 1.0% drops (1 drop 4 times daily for 3 weeks). The postoperative follow‐up was 90 days. The primary outcome was safety, evaluated by the incidence and severity of adverse events. Exploratory measures were anterior chamber cell, anterior chamber flare, and anterior chamber cell–flare clearing. Results : One hundred twenty‐six IBI‐10090 patients and 55 prednisolone patients were included in the safety analysis. Two serious adverse events unrelated to treatment were reported. The decrease in endothelial cell density was not significantly different between groups. The most common adverse events were increased intraocular pressure (11.1%), iritis (6.3%), and systemic (7.9% IBI‐10090 group; 10.9% prednisolone group). By 8 days postoperatively, 51.6% of IBI‐10090 eyes and 50.9% of prednisolone eyes had anterior chamber cell clearing; more than 98% of eyes had clearing at 90 days. The anterior chamber flare and anterior chamber cell–flare clearing results were similar. Of IBI‐10090 patients, 68.7% strongly agreed that not having to use eyedrops was very convenient; 39.2% using prednisolone 1.0% strongly stated they would have preferred dropless therapy. Conclusion : The safety and efficacy of IBI‐10090 and prednisolone 1.0% were similar, with IBI‐10090 preferred over drops.